1991
DOI: 10.3354/meps075101
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of American plaice on the northern Grand Banks

Abstract: In 1985 seasonal surveys were conducted on the northern Grand Banks in NAFO Division 3L to determine if there was seasonal variation in the dstribution of American plaice Hippoglossoides platessoides Fabricius. Plaice were generally most common between 100 and 200 m depth but were more abundant in depths < 100 m in spring than in other seasons. Fish were under-represented at temperatures greater than +1.O0C in all seasons but were much more under-represented at temperatures of -1.2"C and less, in depths of les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The seasonal movements of plaice on the Grand Bank have not been as clearly demonstrated. Morgan & Brodie (1991) found that Grand Bank plaice avoided areas of very low temperature in the winter, and there are some indications from fisheries that these plaice move into deeper (warmer) waters in the winter . However, tagging studies have indicated that Grand Bank plaice are rather sedentary (Pitt 1969, Morgan 1996.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal movements of plaice on the Grand Bank have not been as clearly demonstrated. Morgan & Brodie (1991) found that Grand Bank plaice avoided areas of very low temperature in the winter, and there are some indications from fisheries that these plaice move into deeper (warmer) waters in the winter . However, tagging studies have indicated that Grand Bank plaice are rather sedentary (Pitt 1969, Morgan 1996.…”
Section: Discussionmentioning
confidence: 99%
“…This makes temperature one of the key determinants of habitat quality for fishes (Fry 1971, Reynolds & Casterlin 1979. Numerous studies have demonstrated relationships between temperature and the distribution of fishes (Scott 1982, Mahon et al 1984, Rose & Leggett 1989, Morgan & Brodie 1991.…”
Section: Introductionmentioning
confidence: 99%
“…There are three populations of American plaice living (i) off the east and south coasts of Newfoundland, Labrador, and Northeast Newfoundland (Northwest Atlantic Fisheries Organization, NAFO, Divisions 2J3K), (ii) on the Grand Bank (NAFO Divisions 3LNO), and (iii) on St Pierre Bank (NAFO Division 3Ps). Although there are seasonal movements of plaice in the study area (Morgan and Brodie, 1991), tagging indicates that the fish do not undertake long-distance movements (Morgan, 1996). In particular, the three populations investigated here are thought to be distinct, with little or no movement between them (Bowering et al, 1996;Bowering et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Plaice are also distributed within this depth range during winter and are most abundant at depths of 200 to 400 m with few individuals found at 550 to 728 m (Bowering and Brodie, 1994). In both summer and winter, plaice are most abundant at depths of 100 to 200 m on the northern Grand Banks (Morgan and Brodie, 1991). Although plaice have been found in the deeper waters of the Flemish Pass (Iglesias journal.nafo.int et al, 1996), there is no evidence of mixing between the Flemish Cap and Grand Banks populations (Morgan and Bowering MS, 2004).…”
Section: Introductionmentioning
confidence: 95%